The new cultural history - Hunt, Lynn 1945- Hrsg; Biersack, Aletta (Studies on the history of society and culture, 1989)
Michel Foucault's History of culture / Patricia O'Brien -- Crowds, community, and ritual in the work of E.P. Thompson and Natalie Davis / Suzanne Desan -- Local knowledge, local history : Geertz and beyond / Aletta Biersack -- Literature, criticism, and historical imagination : the literary challenge of Hayden White and Dominick LaCapra / Lloyd S. Kramer -- The American parade : representations of the nineteenth-century social order / Mary Ryan -- Texts, printing, readings / Roger Chartier -- Bodies, details, and the humanitarian narrative / Thomas W. Laqueur -- Seeing culture in a room for a Renaissance prince / Randolph Starn